Tìm x
[4x + 1]5 = [4x + 1]3
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
4x(x-5)-(x-1)(4x-3) = 5
4x2 - 20x - [4x2 - 3x - (4x - 3)] = 5
4x2 - 20x - [4x2 - 3x - 4x + 3] = 5
4x2 - 20x - 4x2 + 3x + 4x - 3 = 5
-13x = 5 + 3
-13x = 8
x = \(\dfrac{\left(-8\right)}{13}\)
a, \(-4x+5+2x-1=3\Leftrightarrow-2x=-1\Leftrightarrow x=\dfrac{1}{2}\)
b, \(-2x+2=2\Leftrightarrow x=0\)
c, \(-2x-6=-8\Leftrightarrow x=1\)
1: Ta có: \(\left(x+3\right)^2-\left(x+2\right)\left(x-2\right)=4x+17\)
\(\Leftrightarrow x^2+6x+9-x^2+4-4x=17\)
\(\Leftrightarrow x=2\)
3: Ta có: \(\left(2x+3\right)\left(x-1\right)+\left(2x-3\right)\left(1-x\right)=0\)
\(\Leftrightarrow2x^2-2x+3x-3+2x-2x^2-3+3x=0\)
\(\Leftrightarrow6x=6\)
hay x=1
4x ( x - 5 ) - ( x - 1 ) ( 4x - 3 ) = 5
<=> 4x2 - 20x - ( 4x2 - 7x + 3 ) = 5
<=> 4x2 - 20x - 4x2 + 7x - 3 = 5
<=> - 13x = 8
<=> x = - 8/13
`4x(x-5)-(x-1) (4x-3)-5=0`
`=> 4x*x - 4x*5 - ( x*4x-3*x-1*4x+ 1*3) -5=0`
`=> 4x^2 - 20x-(4x^2 -3x-4x+3)-5=0`
`=> 4x^2 - 20x-4x^2+3x+4x-3-5=0`
`=>-13x-8=0`
`=> -13x=8`
`=> x=-8/13`
Vậy `x=-8/13`
`4x(x-5)-(x-1)(4x-3)-5 = 0`
`=> 4x^2 - 20x - (4x^2 -3x-4x+3)= 5`
`=> 4x^2 - 20x - 4x^2 + 3x + 4x -3 = 5`
`=> (4x^2 - 4x^2) - (20x - 3x - 4x) = 8`
`=> -13x = 8`
`=> x = -8/13`
(4x-3).(4x+2) + (4x+5).(1-4x) = 2.52
16x2 + 8x - 12x - 6 + 4x - 16x2 + 5 - 20x = 50
(16x2 - 16x2) + ( 8x-12x+4x-20x) - (6-5) = 50
-20x = 50
x = -5/2
\(a,\Rightarrow4x^2-20x-4x^2+3x+4x-3=5\\ \Rightarrow-13x=8\Rightarrow x=-\dfrac{8}{13}\\ b,\Rightarrow3x^2-10x+8-3x^2+27x=-3\\ \Rightarrow17x=-11\Rightarrow x=-\dfrac{11}{17}\\ c,\Rightarrow\left(x+3\right)\left(2-x\right)=0\Rightarrow\left[{}\begin{matrix}x=-3\\x=2\end{matrix}\right.\\ d,\Rightarrow2x\left(4x^2-25\right)=0\\ \Rightarrow2x\left(2x-5\right)\left(2x+5\right)=0\Rightarrow\left[{}\begin{matrix}x=0\\x=\dfrac{2}{5}\\x=-\dfrac{2}{5}\end{matrix}\right.\\ e,Sửa:\left(4x-3\right)^2-3x\left(3-4x\right)=0\\ \Rightarrow\left(4x-3\right)^2+3x\left(4x-3\right)=0\\ \Rightarrow\left(4x-3\right)\left(7x-3\right)=0\Rightarrow\left[{}\begin{matrix}x=\dfrac{3}{4}\\x=\dfrac{3}{7}\end{matrix}\right.\)
a.
4x(x-5) - (x-1)(4x-3)-5=0
4x^2-20x-4x^2+3x+4x+3=0
(4x^2-4x^2)+(-20x+3x+4x)+3=0
13x+3 = 0
13x=-3
x=-3/13
b,
(3x-4)(x-2)-3x(x-9)+3=0
3x^2-6x-4x+8 - 3x^2+27x+3=0
(3x^2-3x^2)+(-6x-4x+27x)+(8+3)=0
17x+11=0
17x=-11
x=-11/17
c, 2(x+3)-x^2-3x=0
2(x+3) - x(x+3)=0
(x+3)(2-x)=0
TH1: x+3 = 0; x=-3
TH2: 2-x=0;x=2
(4x + 1)5 = (4x + 1)3
=> (4x + 1)5 - (4x + 1)3 = 0
=> (4x + 1)3.[(4x + 1)2 - 1] = 0
=> \(\orbr{\begin{cases}\left(4x+1\right)^3=0\\\left(4x+1\right)^2-1=0\end{cases}}\)=> \(\orbr{\begin{cases}4x+1=0\\\left(4x+1\right)^2=1\end{cases}}\)=> \(\orbr{\begin{cases}4x=-1\\4x+1\in\left\{1;-1\right\}\end{cases}}\)=> \(\orbr{\begin{cases}x=-\frac{1}{4}\\4x\in\left\{0;-2\right\}\end{cases}}\)
=> \(\orbr{\begin{cases}x=-\frac{1}{4}\\x\in\left\{0;-\frac{1}{2}\right\}\end{cases}}\)